Attitudes towards epilepsy in the UK population: Results from a 2018 national survey. (February 2019) - Holmes, Emily; Bourke, Siobhan; Plumpton, Catrin
Graphical abstract: Highlights: Stigma towards epilepsy and people with epilepsy was present among the survey sample. The average UK attitude was positive but differed by stigma domains. Negative stereotypes were associated with the least stigma. Risk and safety concerns were associated with the most stigma. Knowledge of epilepsy explained the most variation in attitude and stigma. Abstract: Purpose: To measure stigma resulting from negative attitudes toward epilepsy in the United Kingdom (UK) population. Methods: An online survey of a stratified quota sample of UK adults in July 2018. The primary outcome measure was the 46-item Attitudes and Beliefs about Living with Epilepsy (ABLE) scale, scored on a five-point Likert scale. Items on sociodemographic characteristics, experience of epilepsy, and knowledge of epilepsy were also included. Mean scores were calculated for the ABLE and subscales: risk and safety concerns, personal fear and social avoidance, work and role expectations, and negative stereotypes. Hierarchical regressions tested the association between mean ABLE and subscale scores with sociodemographic and epilepsy related factors. Results: 4000 responded, 3875 responses were included in the analysis. Mean ABLE score was 2.28 (95% CI: 2.26–2.29) (1=no stigma, 5=high stigma). Subscales: risk and safety concerns 3.22 (95% CI: 3.20–3.25), personal fear and social avoidance 2.13 (95% CI: 2.11–2.16), work and role expectations 2.07 (95% CI: 2.05–2.09), and negative stereotypes 1.67 (95% CI: 1.65–1.69). Mean knowledge score was 78% (95% CI: 76.15–77.02). Conclusion: Findings of the first UK national survey of attitudes and beliefs about living with epilepsy suggest relatively low stigma among the sampled population. The subscale with the least stigma was negative stereotypes. Risk and safety concerns were associated with highest stigma. Improving public knowledge about epilepsy has potential to reduce stigma, however this may also raise risk and safety concerns. The results from this project could inform future work to improve awareness and understanding of epilepsy.